From ‘ideals’ to the ‘everyday’: Reimagining futures of hybrid higher education spaces - Pöysä-Tarhonen, Johanna (Proceedings of the International Conference on Networked Learning, 2026)
This conceptual paper engages with the complexities of hybrid learning spaces in contemporary higher education. It conceptualises these spaces as dynamic, socially constructed, and materially entangled practices within the postdigital university. The paper responds to dominant discourses of digital transformation that depict this change primarily as a technical adjustment rather than a pedagogical or cultural process, often overlooking the complexities of everyday pedagogical practice. Central to this approach is a postdigital perspective that highlights the entanglement of human and digital elements in everyday life, rendering binary distinctions between ‘online’ and ‘in-person’ increasingly irrelevant. Framed through the geographies of collaboration, informed by spatial and sociomaterial perspectives, the paper positions hybrid learning spaces as evolving, unfinished, and fluid. Mapping these geographies provides both a methodological and conceptual tool to trace how relational, material, and digital configurations unfold across scales and temporalities, revealing tensions as well as possibilities within hybrid higher education. The paper aligns with the view that current educational narratives—particularly those centred on ‘transformation’—often obscure the contradictions and messiness of actual pedagogical practice. Such narratives tend to portray universities and academic staff as fundamentally flawed and in need of wholesale reform, while overlooking the situated practices that sustain education on a daily basis. By foregrounding the profane acts in education—the ordinary, material, and lived practices of students, educators, and institutions—this paper repositions hybridity not as a product of technological innovation alone, but as a process of continuous negotiation in which ideals, contradictions, and everyday realities converge. Finally, the paper acknowledges the notion of futures-in-the-present to highlight how imagined futures already shape current educational configurations. Within this view, higher education does not move towards a single, predetermined future but unfolds through multiple, contested futures embedded in everyday practices. Thus, it proposes that hybrid, collaborative learning spaces should be understood not as endpoints of design but as unfolding sites of possibility, shaped by diverse learner trajectories and emergent educational relations. Taken together, the paper contributes to recent theoretical debates on space, practice, and technology in networked learning and offers a conceptual foundation for reimagining hybrid higher education as inclusive, socially responsive, and future-oriented.